Poland’s Position on the Investment Development Path - Żak, Katarzyna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2018)
In the modern world based on open national economies, individual countries are closely related and even interdependent in terms of trade, investment flows, labor migration, as well as cooperation at the level of enterprises. The role of enterprises in foreign markets in the form of FDI is growing, while the national economies compete for the inflow of such capital. Due to the fact that since the 1990s Poland has been extensively involved in internationalization processes, it seems important to find answers to the questions: how has the inflow of FDI into the country evolved over the years; what position have Polish investors built in foreign markets during this time; and, finally, what is the current position of Poland on the investment development path. To answer these questions, research tools such as the review of domestic and foreign literature were used and desk research (based on NBP and UNCTAD statistical databases) was carried out to determine the position of the Polish economy in the IDP model. The analyses indicate that since 2008, Poland has been moving towards the third phase of the IDP model in a slow but steady manner.